Lanthanum-lithium-sodium double chromates as ionic conductors - Melnikov, P. [UNESP]; León, C.; Santamaría, J.; Sánchez-Quesada, F. (Elsevier, 1997)
Lanthanum-lithium-sodium double chromates Li1-xNaxLa(CrO4)2 were prepared and analysed by means of admittance spectroscopy. Their a.c. conductivity parameters are correlated with structural details of high and low temperature forms of pure lanthanum-lithium double chromates. Lithium compounds show the lowest conductivity values and the highest activation energy for ion motion, while the sample Li0.5Na0.5La(CrO4)2 exhibits the highest conductivity 10-5 S cm-1 and the lowest activation energy 0.58 eV.
Keywords: Activation energy; Admittance spectroscopy; Alkali metals; Conductivity; Double chromates; Lanthanum